1996
DOI: 10.1103/physrevlett.77.759
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Ordered As Layers on InP(110) Surfaces

Abstract: The structure of arsenic monolayers on InP(110) surfaces has been investigated by combining optical spectroscopy with calculations of the surface atomic structure and optical properties. A highly ordered surface structure is obtained after As deposition at room temperature followed by annealing at 300 ± C. From the excellent agreement between the experimental and theoretical results we conclude that the ordered structure consists of an InAs monolayer on the substrate surface. [S0031-9007(96)00686-2] PACS numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 28 publications
2
14
1
Order By: Relevance
“…11 The additivity of bulk and NP response, as well as the relationship between Re[ ε j ] and ε L,j , can be explained under the hypothesis of a thin anisotropic NP layer, bulk isotropy, and alignment of the optical and crystallographic axes. Previous 085440-3 work defining a surface excess function [26][27][28] is adapted to make the anisotropic response explicit. The ASEF is given by…”
Section: Discussionmentioning
confidence: 99%
“…11 The additivity of bulk and NP response, as well as the relationship between Re[ ε j ] and ε L,j , can be explained under the hypothesis of a thin anisotropic NP layer, bulk isotropy, and alignment of the optical and crystallographic axes. Previous 085440-3 work defining a surface excess function [26][27][28] is adapted to make the anisotropic response explicit. The ASEF is given by…”
Section: Discussionmentioning
confidence: 99%
“…We calculate the optical properties by the sp 3 s ‫ء‬ tightbinding approach, which has proven successful for a number of homopolar surfaces [10][11][12]. To separate the contributions of the two opposite surfaces, which yield different optical properties, a linear cutoff function was used in calculating the optical matrix elements.…”
Section: (Received 8 January 1997)mentioning
confidence: 99%
“…Hence, using a reliable theoretical description it should be possible to relate the optical response to the atomic surface structure. At present, few examples of good agreement between experiments and calculations of the optical response based on the one-electron band structure approximation, employing semiempirical tight-binding [10][11][12] as well as ab initio plane-wave expansions [13], are available. For GaAs(100), however, theoretical results are rather unsatisfactory [14,15], and recently it was hypothesized that RAS line shapes in many cases may have little to do with the atomic structure of the surface, but are rather determined by surface-induced changes of excitonic and local-field effects on bulk transitions [16,17] which are not included in the above mentioned calculations.…”
mentioning
confidence: 99%
“…5 As/InP͑110͒ appears to be another case with a deviating structure. In an optical spectroscopy study, combined with ab initio total-energy calculations 6 it was concluded that an exchange reaction occurs at room temperature between the As and substrate P, leaving an InAs layer on the InP substrate. It was also concluded that this well-ordered phase transforms reversibly into another phase containing a second As overlayer in an ECLS configuration on top of this InAs layer.…”
Section: Introductionmentioning
confidence: 99%